Pengembangan Geopark Nasional Indonesia menuju UNESCO Global Geopark sebagai Diplomasi Geotourism Indonesia - Leonard Felix Hutabarat (Jurnal Ilmiah Hubungan Internasional, 2023)
The development of geopark has been carried out in the last three decades. Since its development by UNESCO, the total number of global geoparks has advanced annually. At country level, Indonesia has only less than 6 (six) UNESCO Global Geoparks compares to its variety of topography in Indonesia, which underlines geological heritage landscapes. Why does Indonesia need to develop more global geoparks and what are the opportunities according to UNESCO requirements? This paper uses the UNESCO global geopark diplomacy and geotourism framework. The method used is qualitative with descriptive analysis. The establishment of national geoparks towards UNESCO Global Geoparks has been seen to be one of an ef ective regional development instruments in a sustainable way. Establishing UNESCO Global Geoparks are not only a way to develop geotourism, but also to develop economic development. The establishment of Indonesian national geoparks to be UNESCO Global Geoparks could be as an engine to provide employments, economic prosperity, public progress as well as environmental protection. Development of Indonesian national geopark to be UNESCO Global Geoparks will be one of strategy in Indonesian geotourism diplomacy as well as Indonesia’s commitment to sustainable development. Keywords: diplomacy; geopark; geotourism; UNESCO Global Geopark